Allograft Cellular Bone Matrix in Extreme Lateral Interbody Fusion: Preliminary Radiographic and Clinical Outcomes. (2nd December 2012) - Tohmeh, Antoine G.; Watson, Blake; Tohmeh, Mirna; Zielinski, Xavier J.
Abstract : Introduction . Extreme lateral interbody fusion (XLIF) is a minimally disruptive alternative for anterior lumbar interbody fusion. Recently, synthetic and allograft materials have been increasingly used to eliminate donor-site pain and complications secondary to autogenous bone graft harvesting. The clinical use of allograft cellular bone graft has potential advantages over autograft by eliminating the need to harvest autograft while mimicking autograft's biologic function. The objective of this study was to examine 12-month radiographic and clinical outcomes in patients who underwent XLIF with Osteocel Plus, one such allograft cellular bone matrix. Methods . Forty (40) patients were treated at 61 levels with XLIF and Osteocel Plus and included in the analysis. Results . No complications were observed. From preoperative to 12-month postoperative followup, ODI improved 41%, LBP improved 55%, leg pain improved 43.3%, and QOL (SF-36) improved 56%. At 12 months, 92% reported being "very" or "somewhat" satisfied with their outcome and 86% being either "very" or "somewhat likely" to choose to undergo the procedure again. Complete fusion was observed in 90.2% (55/61) of XLIF levels. Conclusions . Complete interbody fusion with Osteocel Plus was shown in 90.2% of XLIF levels, with the remaining 9.8% being partially consolidated and progressing towards fusion at 12 months.